Kartu pemantauan pertumbuhan panjang badan dapat meningkatkan nilai z-skor PB/U pada anak stunting - Waliyo, Edy; Agusanty, Shelly Festillia; Nopriantini, Nopriantini (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Stunting in children was largely unknown by parents, because when visited the Posyandu there wasn’t assessment of length growth. The purpose of this study was to provide a card to monitor the lenght growth in children who are stunted against length for age z-skor (LAZ).Method: This type of research was a quasi experimental design pre and posttest control group design using two group: the intervention group was given a length growth monitoring card and and the control group was given a standard child growth chart. This research was conducted in Sambas Subdistrict, Sejangkung Regency for three months. The sample in this study was stunting children aged 3-21 months with a total sample of twenty each group. The dependent variable was LAZ, which is measured before and after the intervention. Statistical analysis was to determine the differences between the two groups after the intervention with the Mann Whitney Test.Results: The results showed that the group given the length growth card was the average value of LAZ before -3.12 ± 0.69 and after the intervention -2.98 ± 0.78 with an increase in the z-score of 0.14 ± 0.68, while the control group LAZ values before -2.68 ± 0.34 and after the intervention -2.62 ± 0.68 with an increase of 0.07 ± 0.633. Statistically with the Man Whitney Test showed no difference, but the change in the LAZ was higher in the group given the growth card compared to the control group.Conclusion: Giving growth cards and child growth charts did not difference in increasing LAZ in stunting children. However providing a growth monitoring card can encourage mothers to feed their children better.